Comparisons of Microleakage and Scanning Electron Microscope SEM Analyzes of The Use of Different Pulp Coverage Materials - Yavuz, Yasemin; Kotanli, Sedef; Doğan, Mehmet Sinan; Doğan, Kemal (UI Scholars Hub, 2022)
Background: The aim of this study was to compare three different pulp coverage materials with calcium silicate content considering microleakage in the cavity floor and evaluate the gaps with a stereomicroscope and scanning electron microscope SEM. Methods: A total of 40 human molar teeth were used in this study, and class V (4 mm mesio-distal × 3 mm gingivo-occlusal × 3 mm depth) cavities were prepared. The samples were divided into four groups (N = 10), including NeoPutty(Nusmile), Biodentin (Septodont), and TheraCal PT (Bisco). All groups were restored using Single Bond Universal adhesive and Filtek Z250 (3M ESPE). The 0.5% basic fuchsin dye leakage was examined at 40× magnification under a stereomicroscope. SEM analysis revealed that the magnification was fixed at 1.00 KX on all the images. The gaps between the pulp coverage material and the cavity floor dentin were measured from four different points. Results: The different microleakage scores were statistically significant (p < 0.05) when the pulp coverage materials were compared considering microleakage. Conclusions: Within the scope of this study, the biocompatible pulp coating materials NeoPutty and Biodentin showed the least microleakage at the cavity floor and the smallest gaps on the dentin material combined surfaces. By contrast, TheraCal showed increased microleakage and large gaps.